Hexagonal boron nitride powder and resin composition
A boron nitride powder with controlled particle size and density enhances filling and insulation in resin compositions, addressing the challenges of existing heat dissipation materials by providing improved thermal and insulating properties for electronic components.
Patent Information
- Application Number
- JP2021049934
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-24
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2041-03-24
AI Technical Summary
Existing heat dissipation materials for electronic components face challenges in achieving high thermal conductivity, insulation, and mechanical stability, particularly when using boron nitride particles, as they often lack sufficient filling amounts and particle size control, leading to aggregation and reduced insulating properties.
A boron nitride powder with specific particle size and tap density relationships, along with controlled moisture content and surface area, is used to enhance filling properties and insulation, suitable for resin compositions in electronic components.
The boron nitride powder allows for easy adjustment of filling amounts, resulting in heat dissipation members with improved insulation and reduced dielectric properties, suitable for high-frequency applications.
Smart Images

Figure 0007623865000001 
Figure 0007623865000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a hexagonal boron nitride powder and a resin composition. [Background technology]
[0002] In electronic components such as transistors, thyristors, and CPUs, efficient dissipation of heat generated during use is an important issue. For this reason, heat dissipation materials with high thermal conductivity are used together with such electronic components. Meanwhile, boron nitride particles have high thermal conductivity and high insulating properties, so they are widely used as a filler in heat dissipation materials.
[0003] For example, Patent Document 1 proposes hexagonal boron nitride powder and a method for producing the same, which, when used as a filler for insulating heat dissipation materials such as resins, can increase the thermal conductivity and withstand voltage (dielectric breakdown voltage) of the resins. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-116401 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, devices equipped with electronic components have become faster in signal transmission and have larger capacity. For this reason, heat dissipation materials that may be exposed to high temperatures during use are also required to have better insulation properties. To fully exert insulation properties, it is desirable for the heat dissipation materials to have low dielectric constants and small dielectric loss tangents.
[0006] As a method for reducing the dielectric constant and dielectric dissipation factor of the heat dissipation member, for example, a resin with a small dielectric constant and dielectric dissipation factor may be used. However, for example, fluororesins, which are known as resins with low dielectric constants and low dielectric dissipation factors, are insufficient in terms of processability, thermal properties, mechanical properties, etc., for the intended use. Therefore, from the viewpoint of improving thermal properties, fillers are generally used, but there may be cases where the amount of filler blended is not sufficient, or the low dielectric dissipation factor characteristics of the resin are not fully exhibited due to the blending of the filler. In addition, it may be possible to increase the filling amount by reducing the average particle size of the filler, but this tends to increase the variation in particle size, and aggregation may occur, which may reduce the filling property.
[0007] An object of the present disclosure is to provide a hexagonal boron nitride powder and a resin composition that allow for easy adjustment of the filling amount and that can be used to produce a heat dissipation component with excellent insulating properties. [Means for solving the problem]
[0008] One aspect of the present disclosure is a composite material comprising primary particles of hexagonal boron nitride, the primary particles having an average particle size of 5 to 15 μm and a tap density (unit: g / cm 3 The present invention provides a hexagonal boron nitride powder in which the tap density and the average particle diameter satisfy the relationship: [tap density]≧0.025×[average particle diameter]+0.55 (1).
[0009] Through extensive research, the inventors have found that a powder having a large tap density that satisfies the relationship of formula (1), such as the above-mentioned hexagonal boron nitride powder, i.e., a powder that can be packed to a density equal to or greater than a predetermined density expected for its particle size, has a particle shape and distribution that are suitable for improving packing properties and insulating properties. In other words, the above-mentioned hexagonal boron nitride powder allows easy adjustment of the packing amount, and is suitable as a material for producing a heat dissipation member with excellent insulating properties.
[0010] The primary particles may have an average thickness of 0.7 to 1.5 μm.
[0011] The hexagonal boron nitride powder may have a moisture content per unit mass of less than 150 ppm when heated to 200°C.
[0012] The above hexagonal boron nitride powder has a specific surface area of 2.5 m 2 / g.
[0013] One aspect of the present disclosure provides a resin composition containing a resin and the above-mentioned hexagonal boron nitride powder.
[0014] The resin composition contains the above-mentioned hexagonal boron nitride powder, and is therefore suitable for producing a heat dissipation member having excellent insulating properties. Effect of the Invention
[0015] According to the present disclosure, it is possible to provide a hexagonal boron nitride powder and a resin composition that allow for easy adjustment of the filling amount and enable the production of a heat dissipation component with excellent insulating properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, embodiments of the present disclosure will be described. However, the following embodiments are merely examples for explaining the present disclosure, and are not intended to limit the present disclosure to the following contents.
[0017] Unless otherwise specified, the materials exemplified in this specification can be used alone or in combination of two or more. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.
[0018] One embodiment of the hexagonal boron nitride powder contains primary particles of hexagonal boron nitride, and the primary particles have an average particle size of 5 to 15 μm. The tap density of the hexagonal boron nitride powder and the average particle size satisfy the relationship of the following formula (1). The following formula (1) is expressed by the formula that [tap density] is g / cm 3The tap density of the hexagonal boron nitride powder is greater than that of conventional hexagonal boron nitride powders having the same average particle size as the primary particles, and the tap density of the hexagonal boron nitride powder is greater than that of conventional hexagonal boron nitride powders having the same average particle size as the primary particles. [Tap density] ≥ 0.025 × [average particle size] + 0.55 (1)
[0019] In the hexagonal boron nitride powder, the lower limit of the average particle size of the primary particles may be, for example, 6.5 μm or more, 7.0 μm or more, 7.5 μm or more, 8.0 μm or more, or 8.5 μm or more. When the lower limit of the average particle size is within the above range, the filling property into the resin and the insulating property of the obtained heat dissipation member can be compatible at a higher level. The upper limit of the average particle size of the primary particles may be, for example, 14.5 μm or less, or 14.0 μm or less. When the upper limit of the average particle size is within the above range, the moldability of the resin composition and the uniformity of its surface can be made good. For example, when the hexagonal boron nitride powder is dispersed in a resin and molded into a sheet, the average particle size of the primary particles may be selected according to the thickness of the sheet.
[0020] The average particle size in this specification is a value obtained by measuring a sample that has been subjected to homogenization of hexagonal boron nitride powder, and is an average particle size that does not include aggregated particles. The average particle size in this specification is also a particle size (median size, d50) at which the cumulative value of the cumulative particle size distribution is 50%. The average particle size in this specification is measured using a laser diffraction scattering particle size distribution measuring device in accordance with the description of ISO 13320:2009. Specifically, it is measured by the method described in the examples of this specification. As the laser diffraction scattering particle size distribution measuring device, for example, "LS-13 320" (device name) manufactured by Beckman Coulter, Inc. can be used.
[0021] The above-mentioned hexagonal boron nitride powder has a relatively large tap density, which is presumably due to the fact that the variation in the average particle size of the primary particles is suppressed. The tap density of the hexagonal boron nitride powder is required to satisfy the relationship of the above formula (1), and the lower limit of the tap density is, for example, 0.70 g / cm. 3 More than 0.75g / cm 3 or more than 0.80g / cm 3 The upper limit of the tap density of the hexagonal boron nitride powder is not particularly limited, but it is preferable that the tap density is equal to or greater than the theoretical density of boron nitride (2.26 g / cm3). 3 ), for example, 1.5g / cm 3 It may be a value of about 1.3 g / cm 3 or less than 1.0g / cm 3 It may be the following:
[0022] In this specification, the "tap density" means a value determined in accordance with the method described in JIS R 1628:1997 "Method for measuring bulk density of fine ceramic powders", and specifically, is determined by the method described in the examples.
[0023] The primary particles of hexagonal boron nitride may have a large thickness. The lower limit of the average thickness of the primary particles may be, for example, 0.7 μm or more, 0.8 μm or more, 0.9 μm or more, or 1.0 μm or more. When the lower limit of the average thickness of the primary particles is within the above range, the fillability of the hexagonal boron nitride powder in a resin or the like can be further improved. The upper limit of the average thickness of the primary particles may be, for example, 2.0 μm or less, 1.5 μm or less, or 1.3 μm or less. When the upper limit of the average thickness of the primary particles is within the above range, the average particle size may be 20 μm or more. The average thickness of the primary particles may be adjusted within the above range, and may be, for example, 0.7 to 1.5 μm, 0.9 to 1.4 μm, or 1.0 to 1.3 μm.
[0024] Hexagonal boron nitride powder can adsorb moisture on its surface. When a periodic electric field is applied to the hexagonal boron nitride powder that has adsorbed moisture, a part of the electric energy can be promoted to be consumed as heat energy, and thus the dielectric loss tangent tends to increase. From the viewpoint of further decreasing the dielectric loss tangent, the hexagonal boron nitride powder may preferably have a low moisture content.
[0025] Moisture on the surface of the hexagonal boron nitride powder can be desorbed by heating to 200° C. The hexagonal boron nitride powder may have a moisture content per unit mass when heated to 200° C. of, for example, less than 150 ppm, 148 ppm or less, or 145 ppm or less.
[0026] The moisture content in this specification means a value measured based on the Karl Fischer method in accordance with the description of JIS K 0068:2001 "Method for measuring moisture content in chemical products". Specifically, first, a predetermined amount of the measurement sample is collected on an air-baked alumina board, and the sample is placed in a furnace thermostatically controlled at 25°C. The moisture generated when the sample is heated to a measurement temperature (200°C) using nitrogen gas as a carrier gas is measured by coulometric titration, and the result obtained is converted to a value per unit mass (1g), thereby determining the moisture content. As a measuring device, for example, "Trace Moisture Measuring Device CA-06" (product name) manufactured by Mitsubishi Chemical Co., Ltd. can be used. As a titration solution, for example, "Aquamicron AX" (product name) manufactured by Mitsubishi Chemical Co., Ltd. can be used as a catholyte, and "Aquamicron CXU" (product name) manufactured by Mitsubishi Chemical Co., Ltd. can be used as an anolyte.
[0027] The upper limit of the specific surface area of the hexagonal boron nitride powder is, for example, 2.5 m 2 / g, less than 2.2m 2 / g or less, 2.0m 2 / g or less, 1.8m 2 / g or less, or 1.6m 2 When the upper limit of the specific surface area is within the above range, adsorption of moisture and the like can be suppressed, and the dielectric tangent can be further reduced. The lower limit of the specific surface area of the hexagonal boron nitride powder is, for example, 0.5 m 2 / g or more, 0.8m 2 / g or more, 1.0m 2 / g or more, 1.2m 2 / g or more, or 1.4m 2 / g or more. The specific surface area of hexagonal boron nitride powder that can be practically synthesized is 0.4 m 2 The specific surface area of the hexagonal boron nitride powder can be adjusted within the above range, for example, 0.3 to 2.5 m 2 / g, or 1.0 to 2.2 m 2 / g.
[0028] The specific surface area in this specification means a value measured using a specific surface area measuring device in accordance with the description of JIS Z 8830:2013 "Method for measuring the specific surface area of powders (solids) by gas adsorption", and is a value calculated by applying the BET single point method using nitrogen gas. More specifically, it is measured by the method described in the Examples.
[0029] It is desirable that the hexagonal boron nitride powder has excellent orientation. The lower limit of the orientation index of the hexagonal boron nitride powder may be, for example, 20 or more, 30 or more, or 35 or more. The upper limit of the orientation index of the hexagonal boron nitride powder may be, for example, 200 or less, 150 or less, or 100 or less.
[0030] The orientation index in this specification means a value measured according to the following method. By performing X-ray diffraction measurement on hexagonal boron nitride powder, peak intensities I(002) and I(100) corresponding to the (002) and (100) planes are obtained from the X-ray diffraction spectrum of the hexagonal boron nitride powder. The obtained peak intensities are used to calculate the orientation index [I(002) / I(100)] of the hexagonal boron nitride powder. More specifically, the measurement is performed according to the method described in the Examples. As an X-ray diffraction device, for example, "ULTIMA-IV" (product name) manufactured by Rigaku Corporation can be used.
[0031] The above-mentioned hexagonal boron nitride powder can be manufactured, for example, by the following method. One embodiment of the manufacturing method of the hexagonal boron nitride powder is a manufacturing method that applies the so-called carbon reduction method, and includes a step of sintering a mixed powder containing a boron-containing compound containing boric acid and a carbon-containing compound under a nitrogen pressure atmosphere to obtain a sintered product containing boron nitride (hereinafter also referred to as a low-temperature sintering step), and a step of heat-treating the sintered product at a temperature higher than the above step and less than 2050°C to generate primary particles of hexagonal boron nitride (hBN) (hereinafter also referred to as a sintering step).
[0032] A boron-containing compound is a compound having boron as a constituent element. A raw material having high purity and relatively low cost can be used as the boron-containing compound. In addition to boric acid, examples of such a boron-containing compound include boron oxide. The boron-containing compound contains boric acid, which is dehydrated by heating to become boron oxide, which forms a liquid phase during the heat treatment of the raw material powder and can also function as an auxiliary agent for promoting grain growth.
[0033] A carbon-containing compound is a compound having carbon atoms as a constituent element. As the carbon-containing compound, a raw material having high purity and relatively low cost can be used. Examples of such carbon-containing compounds include carbon black and acetylene black. The specific surface area of the carbon black used is 250 m. 2 / g or less than 200m 2 When the specific surface area of the carbon black is within the above range, the growth of the primary particles of boron nitride can be further promoted, making it easier to prepare a hexagonal boron nitride powder with a small specific surface area.
[0034] In the mixed powder, the boron-containing compound may be blended in an excess amount relative to the carbon-containing compound. The mixed powder may contain other compounds in addition to the carbon-containing compound and the boron-containing compound. Examples of other compounds include boron nitride as a nucleating agent. When the mixed powder contains boron nitride as a nucleating agent, the average particle size of the synthesized hexagonal boron nitride powder can be more easily controlled. The mixed powder preferably contains a nucleating agent. When the mixed powder contains a nucleating agent, a hexagonal boron nitride powder with a small specific surface area (for example, a hexagonal boron nitride powder with a specific surface area of 2.5 m) is preferably used. 2 / g or less) can be more easily prepared.
[0035] The low-temperature sintering step is carried out under pressure. The pressure in the low-temperature sintering step may be, for example, 0.25 MPa or more and less than 5.0 MPa, 0.25 to 3.0 MPa, 0.25 to 2.0 MPa, 0.25 to 1.0 MPa, 0.25 MPa or more and less than 1.0 MPa, 0.30 to 2.0 MPa, or 0.50 to 2.0 MPa. By increasing the pressure in the low-temperature sintering step, the volatilization of raw materials such as boron-containing compounds can be further suppressed, and the generation of boron carbide, which is a by-product, can be suppressed. In addition, by increasing the pressure in the low-temperature sintering step, the increase in the specific surface area of the boron nitride powder can be suppressed. By setting the upper limit of the pressure in the low-temperature sintering step within the above range, the growth of primary particles of boron nitride can be further promoted.
[0036] The heating temperature in the low-temperature firing step may be, for example, 1650° C. or higher and lower than 1800° C., 1650 to 1750° C., or 1650 to 1700° C. By setting the lower limit of the heating temperature in the low-temperature firing step within the above range, the reaction can be promoted and the yield of the obtained boron nitride can be improved. By setting the upper limit of the heating temperature in the low-temperature firing step within the above range, the generation of by-products can be sufficiently suppressed.
[0037] The heating time in the low-temperature firing step may be, for example, 1 to 10 hours, 1 to 5 hours, or 2 to 4 hours. In the step at the beginning of the reaction to synthesize boron nitride, by maintaining a relatively low temperature for a predetermined time, the reaction system can be made more homogenous, and the boron nitride formed can be made more homogenous. In this specification, the heating time means the time (retention time) during which the temperature of the ambient environment of the heated object is maintained at a predetermined temperature after the temperature reaches the predetermined temperature.
[0038] The sintering process is a process in which the sintered product obtained in the low-temperature sintering process is heat-treated at a temperature higher than that in the low-temperature sintering process to generate primary particles of hexagonal boron nitride (hBN), and a powder containing agglomerated particles constituted by the agglomeration of the primary particles is obtained.
[0039] The heating temperature in the firing step is higher than that in the low-temperature firing step and is less than 2050°C. By setting the heating temperature in the firing step within the steam range, the graphitization index can be further increased, and hexagonal boron nitride with excellent crystallinity can be obtained. The heating temperature in the firing step may be 2000°C or less. The heating time in the firing step may be, for example, 3 to 15 hours, 5 to 10 hours, or 6 to 9 hours.
[0040] The pressure in the firing step may be, for example, 0.25 MPa or more and less than 5.0 MPa, 0.25 to 3.0 MPa, 0.25 to 2.0 MPa, 0.25 to 1.0 MPa, 0.25 MPa or more and less than 1.0 MPa, 0.30 to 2.0 MPa, or 0.50 to 2.0 MPa. By increasing the pressure in the firing step, the purity of the obtained raw material powder can be further improved. By setting the upper limit of the pressure in the firing step within the above range, the preparation cost of the raw material powder can be further reduced, which is industrially advantageous.
[0041] By the above steps, hexagonal boron nitride powder can be obtained. A pulverization step may be performed after the low-temperature firing step or the firing step. In the pulverization step, a general pulverizer or crusher can be used.
[0042] The hexagonal boron nitride powder according to the present disclosure has excellent packing properties and a low dielectric tangent, and can therefore be used in applications where high-frequency voltage is applied. The hexagonal boron nitride powder according to the present disclosure is suitable, for example, as a filler for a resin composition used in electronic components that constitute a high-frequency circuit. One embodiment of the resin composition contains a resin and the above-mentioned hexagonal boron nitride powder.
[0043] The lower limit of the content of the hexagonal boron nitride powder may be, for example, 30% by volume or more, 40% by volume or more, or 50% by volume or more, based on the total volume of the resin composition. When the lower limit of the content of the hexagonal boron nitride powder is within the above range, the thermal conductivity of the resin composition can be improved and excellent heat dissipation performance can be obtained. The upper limit of the content of the hexagonal boron nitride powder may be, for example, 85% by volume or less, 80% by volume or less, or 70% by volume or less, based on the total volume of the resin composition. When the upper limit of the content of the hexagonal boron nitride powder is within the above range, it is possible to further suppress the generation of voids inside the resin composition during molding, and also to suppress the deterioration of insulation and mechanical strength.
[0044] Examples of resins include liquid crystal polymers, fluororesins, silicone resins, silicone rubber, acrylic resins, polyolefins (polyethylene, etc.), epoxy resins, phenolic resins, melamine resins, urea resins, unsaturated polyesters, polyimides, polyamideimides, polyetherimides, polybutylene terephthalate, polyethylene terephthalate, polyphenylene ether, polyphenylene sulfide, wholly aromatic polyesters, polysulfones, polyethersulfones, polycarbonates, maleimide-modified resins, ABS (acrylonitrile-butadiene-styrene) resins, AAS (acrylonitrile-acrylic rubber-styrene) resins, and AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resins.
[0045] The resin content may be 15 vol% or more, 20 vol% or more, or 30 vol% or more, and may be 70 vol% or less, 60 vol% or less, or 50 vol% or less, based on the total volume of the resin composition.
[0046] The resin composition may further contain a curing agent that cures the resin. The curing agent may be appropriately selected depending on the type of resin. For example, when the resin is an epoxy resin, the curing agent may be, for example, a phenol novolac compound, an acid anhydride, an amino compound, and an imidazole compound. The content of the curing agent may be, for example, 0.5 parts by mass or more or 1.0 parts by mass or more, and 15 parts by mass or less or 10 parts by mass or less, relative to 100 parts by mass of the resin.
[0047] Although several embodiments have been described above, the present disclosure is not limited to the above-described embodiments. In addition, the descriptions of the above-described embodiments can be mutually applied. EXAMPLES
[0048] The present disclosure will be described in more detail below using examples and comparative examples. Note that the present disclosure is not limited to the following examples.
[0049] Example 1 [Preparation of hexagonal boron nitride powder] Boric acid (manufactured by Kojundo Chemical Laboratory Co., Ltd.) 100 parts by mass, acetylene black (manufactured by Denka Co., Ltd., grade name: FX-35, specific surface area: 130 m 2 A mixed powder (raw material powder) was obtained by mixing 22 parts by mass of sodium hydroxide (0.1% by mass / g) and 1 part by mass of sodium carbonate (purity 99.5% by mass or more) using a Henschel mixer. The obtained mixed powder was placed in a dryer at 250°C and held for 3 hours to dehydrate the boric acid. The dehydrated mixed powder was placed in a mold with a diameter of 100Φ in a press molding machine and molded under the conditions of a heating temperature of 200°C and a pressing pressure of 30 MPa. The pellets of the raw material powder obtained in this manner were subjected to the subsequent heat treatment.
[0050] First, the pellets were placed in a carbon atmosphere furnace, and the temperature was increased to 1750°C at a heating rate of 5°C / min in a nitrogen atmosphere pressurized to 0.65 MPa, and the pellets were heat-treated at 1750°C for 3 hours to obtain a first heat-treated product (first step). Next, the temperature in the carbon atmosphere furnace was further increased to 1800°C at a heating rate of 2°C / min, and the first heat-treated product was heat-treated by holding at 1800°C for 3 hours to obtain a second heat-treated product (second step). After that, the temperature in the carbon atmosphere furnace was further increased to 2050°C at a heating rate of 2°C / min, and the second heat-treated product was fired at a high temperature by holding at 2050°C for 7 hours (third step). The loosely aggregated boron nitride after firing was crushed with a Henschel mixer, and the crushed powder was dried at 250°C for 5 hours using a vacuum dryer, and then passed through a sieve with a mesh size of 63 μm to obtain a powder that passed through the sieve. In this manner, hexagonal boron nitride powder was prepared.
[0051] <Physical property measurement of hexagonal boron nitride powder> The obtained hexagonal boron nitride powder was measured for the average particle size of the primary particles, tap density, purity, average thickness of the primary particles, moisture content when heated to 25 to 200° C., specific surface area, and orientation index according to the methods described below. The results are shown in Table 1.
[0052] [Average particle size of primary particles] The average particle size of the primary particles in the hexagonal boron nitride powder was measured using a laser diffraction scattering particle size distribution analyzer (manufactured by Beckman Coulter, Inc., device name "LS-13 320") in accordance with the description of ISO 13320:2009. In addition, when measuring the hexagonal boron nitride powder, an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, product name "US-300E") was used to perform ultrasonic dispersion at AMPLITUDE (amplitude) 80% once for 1 minute 30 seconds to prepare a dispersion liquid of the hexagonal boron nitride powder, which was used as the measurement subject. When measuring the particle size distribution, water was used as the solvent for dispersing the hexagonal boron nitride powder, and hexametaphosphoric acid was used as the dispersant. In this case, a value of 1.33 was used as the refractive index of water, and a value of 1.80 was used as the refractive index of the boron nitride powder.
[0053] [Tap Density] The tap density with hexagonal boron nitride powder was measured in accordance with the method described in JIS R 1628:1997 "Method of measuring bulk density of fine ceramic powders." Specifically, the hexagonal boron nitride powder was tapped at 100 cm 3 The bulk density was measured after tapping under the conditions of tapping time 180 seconds, tapping number 180 times, and tap lift 18 mm. The measured value was the tap density. The measurement was performed using a commercially available device (Powder Tester, manufactured by Hosokawa Micron).
[0054] [purity] Hexagonal boron nitride powder was decomposed with sodium hydroxide, and ammonia was distilled from the decomposition liquid by steam distillation and collected in an aqueous boric acid solution. This collected liquid was titrated with a normal sulfuric acid solution. The nitrogen atom (N) content in the boron nitride powder was calculated from the titration results. The hexagonal boron nitride (hBN) content in the boron nitride powder was determined from the obtained nitrogen atom content based on formula (2), and the purity of the hexagonal boron nitride powder was calculated. The formula weight of hexagonal boron nitride was 24.818 g / mol, and the atomic weight of the nitrogen atom was 14.006 g / mol. Hexagonal boron nitride (hBN) content in sample [mass%] = nitrogen atom (N) content [mass%] × 1.772 (2)
[0055] [Average thickness of primary particles] The average thickness of the primary particles of hexagonal boron nitride was measured according to the following method. 3 g of hexagonal boron nitride powder was molded into a disk shape (diameter: 30 mmφ) at a pressure of 5 MPa using a press molding machine (manufactured by Rigaku Corporation, product name: BRE-32). The obtained molded body was embedded using resin (manufactured by GATAN, product name: G2 epoxy). Next, a sample in which the cross section of the primary particles of hexagonal boron nitride was exposed was prepared by performing cross-sectional milling in a direction parallel to the direction of pressure application. This cross section was photographed using a scanning electron microscope (manufactured by JEOL Ltd., product name: JSM-6010LA). The obtained particle image was imported into image analysis software (manufactured by Mountec Co., Ltd., product name: Mac-View), and the short side of the rectangular particles (corresponding to the particle thickness and particle short diameter) was measured from the obtained photograph. The measurement was performed on 100 arbitrarily selected primary particles. This was taken as the aspect ratio. In this way, the average thickness of the primary particles was determined.
[0056] [Moisture content] The moisture content of the hexagonal boron nitride powder was measured by the Karl Fischer method when it was heated to 25 to 200° C. and when it was heated to 201 to 500° C. First, a predetermined amount of the measurement sample was collected on an air-baked alumina board, and this was placed in a furnace thermostated at 25° C. The moisture generated when it was heated from 25° C. to the measurement temperature (200° C. or 500° C.) was measured by coulometric titration, and the obtained results were converted per unit mass (1 g) to determine the moisture content (unit: ppm).
[0057] [Specific surface area] The specific surface area of the hexagonal boron nitride powder was calculated by applying the BET single point method using nitrogen gas in accordance with the description in JIS Z 8830:2013 "Method for measuring the specific surface area of powders (solids) by gas adsorption." The specific surface area measurement device used was a specific surface area measurement device (device name: Cantorsorb) manufactured by Yuasa Ionics Co., Ltd. The measurement was performed after drying and degassing the boron nitride powder at 300°C for 15 minutes.
[0058] [Orientation index] The orientation index of hexagonal boron nitride powder was measured according to the following method. For the measurement, an X-ray diffractometer (manufactured by Rigaku Corporation, product name: ULTIMA-IV) was used. First, a measurement sample was prepared by filling and solidifying hexagonal boron nitride powder into the recess of a glass cell with a depth of 0.2 mm attached to the X-ray diffractometer. The measurement sample was irradiated with X-rays, and the peak intensities of the (002) and (100) planes of the measurement sample after baseline correction were determined, and the ratio [I(002) / I(100)] was taken as the orientation index.
[0059] <Evaluation of packing properties of hexagonal boron nitride powder> The filling property of the obtained hexagonal boron nitride powder was evaluated when it was used as a filler. Specifically, the hexagonal boron nitride powder was mixed with silicone oil KF96-100 manufactured by Shin-Etsu Chemical Co., Ltd. so that the amount was 20% by volume, and a slurry was prepared by stirring at 2000 rpm for 3 minutes using a Thinky Rentaro RE-310 foam remover. The viscosity of the slurry was measured using a rheometer manufactured by Nippon Signal Hegner Co., Ltd. (product name: MCR300, circular flat plate (diameter: 25 mmφ), gap: 1 m), and the filling property was evaluated based on the obtained results based on the following criteria. The results are shown in Table 1. A: The viscosity is 5000 mPa s or less at a shear rate of 20 rpm. B: The viscosity at a shear rate of 20 rpm is greater than 5,000 mPa s and less than 10,000 mPa s. C: The viscosity at a shear rate of 20 rpm is greater than 10,000 mPa s and less than 15,000 mPa s. D: Viscosity exceeds 15,000 mPa·s at a shear rate of 20 rpm.
[0060] <Evaluation of dielectric properties of hexagonal boron nitride powder> The dielectric loss tangent of the obtained hexagonal boron nitride powder was measured when it was used as a filler. Specifically, the dielectric loss tangent of the hexagonal boron nitride powder at 1 GHz was obtained by performing measurements at a temperature of 25°C using a cavity resonator method measuring device (Keycom measurement system, perturbation method, cavity resonator type DPS18). The results are shown in Table 1.
[0061] <Evaluation of the insulating properties of hexagonal boron nitride powder> As an evaluation of the properties of the obtained boron nitride powder as a filler for resin, the insulating properties were evaluated when the obtained hexagonal boron nitride powder was used as a filler. Specifically, the dielectric constant and dielectric loss tangent were measured when the hexagonal boron nitride powder was used as a filler. A mixture of 100 parts of naphthalene-type epoxy resin (manufactured by DIC Corporation, product name: HP4032) and 10 parts of imidazoles (manufactured by Shikoku Chemical Industry Co., Ltd., product name: 2E4MZ-CN) as a curing agent was 100 volume %, and hexagonal boron nitride powder was mixed to 55 volume % to prepare a mixture. Next, the above mixture was sieved through a filter with an opening of 150 μm, and then applied to a PET sheet to a thickness of 0.20 mm, and then degassed under reduced pressure of 500 Pa for 10 minutes. Then, the mixture was subjected to a temperature of 150 °C and a pressure of 160 kg / cm 2 The sheet was heated and pressed for 60 minutes under these conditions to produce a 0.10 mm thick sheet. The dielectric breakdown voltage of the produced sheet was measured in accordance with the description in JIS C 6481:1996 "Test methods for copper-clad laminates for printed wiring boards." For the measurement, a withstand voltage and insulation tester (product name: TOS 8650) manufactured by Kikusui Electronics Co., Ltd. was used, and 100 samples were measured, with the arithmetic average value being regarded as the dielectric breakdown voltage. The results are shown in Table 1. A: The dielectric breakdown voltage is 60 kV / mm or more. B: The dielectric breakdown voltage is 40 kV / mm or more and less than 60 kV / mm. C: The dielectric breakdown voltage is less than 40 kV / mm.
[0062] Example 2 The raw material, acetylene black, was converted to acetylene black (manufactured by Denka Co., Ltd., grade name: Li400, specific surface area: 40 m 2 Hexagonal boron nitride powder was prepared in the same manner as in Example 1, except that the mass ratio of the hexagonal boron nitride powder was changed to 0.15 / g, 1 mass% of boron nitride powder (manufactured by Denka Company Ltd., Denka boron nitride powder, grade name: MGP) was added to the raw materials, and the pressure in the carbon atmosphere furnace was changed to 0.85 MPa.
[0063] Example 3 The raw material, acetylene black, was converted to acetylene black (manufactured by Denka Co., Ltd., grade name: Li400, specific surface area: 40 m 2 A hexagonal boron nitride powder was prepared in the same manner as in Example 1, except that the temperature was changed to 0.15 / g and the pressure in the carbon atmosphere furnace was changed to 0.85 MPa.
[0064] Example 4 A hexagonal boron nitride powder was prepared in the same manner as in Example 1, except that the pressure inside the carbon atmosphere furnace was changed to 0.90 MPa.
[0065] For the hexagonal boron nitride powders obtained in Examples 2 to 4, the average particle size of the primary particles, tap density, purity, average thickness of the primary particles, moisture content when heated to 25 to 200°C, specific surface area, and orientation index were measured in the same manner as in Example 1. For the hexagonal boron nitride powders obtained in Examples 2 to 4, the packing property and insulating property were evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0066] [Table 1]
[0067] Comparative Example 1 100 parts by mass of boric acid powder (purity 99.8% by mass or more, manufactured by Kanto Chemical Co., Ltd.), 9 parts by mass of melamine powder (purity 99.0% by mass or more, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), and 13 parts by mass of sodium carbonate (purity 99.5% by mass or more) as an auxiliary agent were added and mixed for 10 minutes using an alumina mortar to obtain a mixed powder. The dried mixed powder was placed in a container made of hexagonal boron nitride and placed in an electric furnace. While circulating nitrogen gas in the electric furnace, the temperature was raised from room temperature to 1000°C at a heating rate of 10°C / min. After holding at 1000°C for 2 hours, heating was stopped and the material was allowed to cool naturally. When the temperature reached 100°C or less, the electric furnace was opened. In this way, a calcined product containing low-crystalline hexagonal boron nitride was obtained.
[0068] 100 g of the above calcined product was placed in the electric furnace. While circulating nitrogen gas in the electric furnace, the temperature was raised from room temperature to 1800°C at a rate of 10°C / min. After maintaining the calcination temperature of 1800°C for 4 hours, heating was stopped and the product was allowed to cool naturally. When the temperature reached 100°C or less, the electric furnace was opened. The calcined product obtained was collected and pulverized in an alumina mortar for 10 minutes to obtain a coarse powder containing hexagonal boron nitride.
[0069] Next, in order to remove impurities contained in the coarse powder, 30 g of the coarse powder was added to 500 g of dilute nitric acid (nitric acid concentration: 5% by mass) and stirred at room temperature for 60 minutes. After stirring, solid-liquid separation was performed by suction filtration, and the water was replaced until the filtrate became neutral, and finally, washing was performed until the electrical conductivity of the washing liquid was 1 mS / m or less. After washing, the powder was dried at 120°C for 3 hours using a dryer to obtain a dry powder. After drying, the powder was sieved through a sieve with 200 μm mesh, and the obtained powder was used as the hexagonal boron nitride powder of Comparative Example 1.
[0070] Comparative Example 2 A hexagonal boron nitride powder was prepared in the same manner as in Comparative Example 1, except that the firing temperature was changed to 1700° C. and the powder was crushed in a ball mill for 2 hours after firing.
[0071] Comparative Example 3 Hexagonal boron nitride powder was prepared in the same manner as in Comparative Example 1, except that calcium carbonate was used instead of sodium carbonate and the firing conditions were changed to 2050° C. and 35 hours.
[0072] Comparative Example 4 Hexagonal boron nitride powder was prepared in the same manner as in Comparative Example 1, except that the firing temperature was changed to 1700°C, the dried powder obtained by acid treatment and drying was placed again in the electric furnace, and the temperature was raised from room temperature to 2000°C at a heating rate of 10°C / min while circulating nitrogen gas through the electric furnace, and the firing temperature of 2000°C was maintained for 4 hours, and the powder after firing (hexagonal boron nitride powder of Comparative Example 4) was collected.
[0073] Comparative Example 5 A hexagonal boron nitride powder was prepared in the same manner as in Comparative Example 1, except that the blending amount of sodium carbonate was changed to 20 parts by mass and the firing temperature was changed to 1850°C.
[0074] Comparative Example 6 The raw material, acetylene black, was converted to acetylene black (manufactured by Denka Co., Ltd., grade name: SAB, specific surface area: 370 m 2 A hexagonal boron nitride powder was prepared in the same manner as in Example 1, except that the content of hexagonal boron nitride in the powder was changed to 0.1 g.
[0075] For the hexagonal boron nitride powders obtained in Comparative Examples 1 to 6, the average particle size of the primary particles, tap density, purity, average thickness of the primary particles, moisture content when heated to 25 to 200°C, specific surface area, and orientation index were measured in the same manner as in Example 1. For the hexagonal boron nitride powders obtained in Comparative Examples 1 to 6, the packing property and insulating property were evaluated in the same manner as in Example 1. The results are shown in Table 2.
[0076] [Table 2]
[0077] In Table 2, “- ※ " means that the filter was clogged and measurement was not possible. [Industrial Applicability]
[0078] According to the present disclosure, it is possible to provide a hexagonal boron nitride powder and a resin composition that allow for easy adjustment of the filling amount and enable the production of a heat dissipation component with excellent insulating properties.
Claims
1. It contains primary particles of hexagonal boron nitride, and the average particle size of the primary particles is 5 to 15 μm, The average thickness of the primary particles is 0.7 to 1.5 μm, The tap density and the average particle size are [Tap density] ≧ 0.025 × [average particle size] + 0.55 ... (1) Hexagonal boron nitride powder that satisfies the relationship.
2. 2. The hexagonal boron nitride powder according to claim 1, which has a moisture content per unit mass of less than 150 ppm when heated to 200°C.
3. Specific surface area is 2.5m 2 3. The hexagonal boron nitride powder according to claim 1 or 2, wherein the Cr content is less than 1 / g.
4. A resin composition comprising a resin and the hexagonal boron nitride powder according to any one of claims 1 to 3.
Citation Information
Patent Citations
Hexagonal boron nitride powder, method for producing the same, resin composition and resin sheet
JP2018104260A
Hexagonal crystal boron nitride powder and method for producing the same, and composition and heat dissipation member using the same
JP2019116401A
Hexagonal boron nitride powder and method for producing hexagonal boron nitride powder
WO2020032060A1